2012
DOI: 10.1007/s00198-012-2032-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisations for fracture and associated costs between 2000 and 2009 in Ireland: a trend analysis

Abstract: Hospitalisations for osteoporotic-type fractures continued to increase in Ireland. Hip fractures increased by 7 % in women and 20 % in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…McGowan and colleagues (2013) (43) (47) 1988-2002 R(Cantabria) þ2.8 þ3 þ2.8 Arias and colleagues (2013) (48) 2002-2008…”
Section: North Americamentioning
confidence: 99%
See 1 more Smart Citation
“…McGowan and colleagues (2013) (43) (47) 1988-2002 R(Cantabria) þ2.8 þ3 þ2.8 Arias and colleagues (2013) (48) 2002-2008…”
Section: North Americamentioning
confidence: 99%
“…(43) Hip fracture trends in Austria were examined for the entire Austrian population aged 50 years and above between 1989 and 2008. (44) In women, the age-standardized incidence increased Fig.…”
Section: Central Europementioning
confidence: 99%
“…Assum ing a constant agestandardized fracture incidence, McGowan et al estimate that by 2025 the absolute numbers of osteo porotic and hip fractures in Ireland will rise by 79% and 88%, respectively. The validity of this assumption is open to debate as several studies, including that by McGowan and col leagues, 3 have shown evidence of a tendency for age standardized rates to be declining. The error in this assumption is, how ever, likely to be small in comparison with the effect of the changing population demo graphics, and the estimates reached are very much in keeping with projections for other European countries.…”
Section: H Edwards and C Coopermentioning
confidence: 96%
“…In one European country, Ireland, McGowan and colleagues give a unique insight into the trends in fracture incidence and burden in the past decade and also provide projec tions for the absolute number of fragility fractures up to 2025. 3 In acute public hospitals across Ireland, data on the absolute number of fragility fractures occurring each year from 2000 to 2009 were collected using a national database of coded discharge summaries, the Hospital InPatient Enquiry system.…”
Section: H Edwards and C Coopermentioning
confidence: 99%
“…Hip fractures are regarded as the most severe type of fragility fracture with a 20-30% mortality rate within one year of fracture (McGowan et al, 2013). NICE guidelines also show that approximately 20% of people who were previously living in the community are discharged directly to nursing homes post hip fractures.…”
Section: Introductionmentioning
confidence: 99%